The Relationship Between Emotional Regulation And Performance Resilience Of Female Volleyball Athletes From H2R Pekanbaru - Cahya Sumantri; Agus Sulastio; Wedi S (Pendidikan Kepelatihan Olahraga FKIP Universitas Riau, 2024)
The problem in this research is the frequent losses experienced by the athletes, which are attributed to mental factors during matches. The purpose of this study is to examine the relationship between emotional regulation and resilience. This research is quantitative, using a correlational design to investigate the relationship between the two variables. The data includes the entire population of 26 athletes. The instruments used in this study are the Emotion Regulation Questionnaire (ERQ) and a questionnaire. The normality test results show that both emotional regulation and resilience variables are normally distributed, with asymp. Sig. 2-tailed values of 0.200 and 0.126, respectively (ρ > 0.05). The results for the two variables indicate a correlation coefficient of 0.798. Since the value is close to 1, the relationship between emotional regulation and resilience can be considered strong. The result shows a positive significance value (2-tailed) of 0.00, meaning that when emotional regulation is high, resilience during matches increases. The conclusion of this study demonstrates a significant relationship between emotional regulation and the performance resilience of H2R Pekanbaru female volleyball athletes. This means that the better the athletes' emotional regulation, the higher their level of resilience in competitions.